Improving pervasive decision support system in critical care by using technology acceptance model - Nunes, Ana (2018)
The increase in the use of technologies in the health area and the evolution of their characteristics became an essential aspect for increasing knowledge in this area, especially in intensive medicine. This aspect is critical for the treatment of high-risk patients, so it became necessary to study the factors that influence the acceptance of the technologies. The INTCare is one technologic healthcare platform that is used in intensive medicine at the Hospital Centre of Porto. This article analyses the INTCare system, the technology acceptance model (TAM) methodology and its application in the preferred system. This analysis is the third already done to this platform, and it comes with the purpose of verifying if the improvements detected in the previous evaluation were carried out successfully and of finding new enhancements. As a result, a questionnaire was developed, with a total of 49 questions, where each one corresponds to at least one TAM construct. This paper allows understanding how systems features can be mapped to the TAM model and how the questionnaires can be used to support it.